Spherical harmonics for surface parametrisation and remeshing - Nortje, Caitlin R.; Ward, Wil O.C.; Neuman, Bartosz P.; Bai, Li (Hindawi Publishing Corporation, 2015)
This paper proposes a novel method for parametrisation and remeshing incomplete and irregular polygonal meshes. Spherical harmonics basis functions are used for parametrisation. This involves least squares fitting of spherical harmonics basis functions to the surface mesh. Tikhonov regularisation is then used to improve the parametrisation before remeshing the surface. Experiments show that the proposed techniques are effective for parametrising and remeshing polygonal meshes.